Bi-objective optimization and thermal economy analysis of a novel coke quenching process with wastewater gasification. (25th January 2023) - Li, Zhen; Zhang, Xinru; Jiang, Zeyi; Wu, Liang; Lai, Nien-Chu
Highlights: An exergy-and-cost bi-objective model for a new coke quenching process is proposed. The parameters of furnace structure and cooling medium flowrate are considered. The best processes under different objective weight schemes are obtained. Higher weights on annual cost than exergy income could bring greater profits. Annual profit of the new process reaches 1.41 times of that via coke dry quenching. Abstract: Coke wastewater gasification quenching (CWGQ) process with waste heat recovery and wastewater treatment has a good application prospect. The process optimization considering the exergy and cost contributes to its economic evaluation and future application. In this work, a bi-objective optimization model of the CWGQ process is established to find the best structural and operating parameters under the comprehensive optimization of net exergy income and total annual cost. We focus on the influence of the weights of objective functions on the optimization result. With the same weight for the two objective functions, the optimal structural parameters of height-to-diameter ratio and volume ratio are 0.267 and 0.723, respectively, while the optimal operating parameters of injected wastewater flowrate and intermediate steam extraction rate are 0.239 t-water/t-coke and 0.364, respectively. The optimal structural parameters are independent of the weights of objective functions. In contrast, the reduction rate of operating parameters at high-weight net exergy income is about 2 times of the increase rate at high-weight total annual cost. When the total annual cost is more significant, the net annual profit gets greater via the CWGQ process, which is 1.41 times of that via widely used coke drying quenching process.